BODY, SEXUALITY, GENDER AND CULTURAL MEDIATIONS IN YOUNG WOMEN'S MAGAZINES: ISSUES ON SEXUAL AND REPRODUCTIVE HEALTH - Bartira Reis Rocha Cezar; Eliane Portes Vargas (Universidade do Estado do Rio de Janeiro, 2016)
Actions on sexual and reproductive health care have required a constant dialogue between schools and health services. The increase in the number of actions of this nature requires improvement of interdisciplinary approaches and the development of appropriate methodologies for education aimed at youngsters involving sexuality, whether in the school environment or through health services. This ethnographic study is guided by anthropological and sociological perspectives that aggregate theoretical contributions of Reception Studies in the field of Social Communication. Through the combination of these perspectives, an analysis of the concepts of body and sexuality has been carried out, stemming from the critical perceptions attributed to two young women's magazines, "Capricho" and "Atrevida", among schoolchildren from 12 to 16 years old in a public school at Baixada Fluminense-RJ. Acknowledging magazines as cultural mediations in the communication / education process, gender relations involved in conceptions about preventive and sexual practices have also been considered. A greater understanding of the guiding logic of conceptions among youngsters has shown to be relevant to the formulation of public policies concerning health and education. The results indicate the relevance of these reflections produced in the critical and reflective activities involving cultural products and their application methodologies in educational practices within the field of health and biosciences, regarding formal and non-formal teaching. The contextualized use of such magazines with youngsters has indicated its potential in the analysis of cultural mediations and in expanded discussions on sexual and reproductive health among youngsters upon their initial experimentation on sexuality. DOI: 10.12957/demetra.2016.22194